The Consequences of Parental Neglect to A Child: A Psychoanalytical Criticism on Lionel Shriver’s Novel We Need to Talk About Kevin - Yeni, Marliza; Khairan, Raisya Arfi (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2026)
Parent – children relationship plays an important role in a child’s personality. This article elaborates the impacts of parental neglect on a child as reflected in Lionel Shriver’s novel We Need to Talk About Kevin. The research applies psychoanalytic literary criticism, utilizing Sigmund Freud’s theory of human psyche (id, ego, and superego) and Erik Erikson’s theory of psychosocial development. The data are collected by using library research method, taking description, narrative and dialogue in the novel related with parental neglect and its effect as primary data, by focusing on the characters of Eva, the mother, and Kevin, the son. Descriptive analysis method is applied in analyzing the data. The result of analysis shows that Eva’s maternal ambivalence reflects her inner conflict between personal freedom and parental responsibility, while her emotional alienation from Kevin represents her fear of intimacy in forming a secure bond with her own child. Eva’s emotional neglect affects Kevin’s psychosocial development negatively in the first five stages, resulting him to develop a psychological impairment and behavioral problems, marked by destructive and manipulative behavior. Through this novel, readers can learn how parental neglect can deeply affects a child’s growth, underlining the importance of a secure emotional relationship between caregivers and the children.